Association between husband support, maternal anxiety, and childbirth preparedness among third-trimester pregnant women - Siti Haryani; Cucuk Kunang Sari (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Childbirth is often accompanied by psychological challenges, particularly anxiety among women in the third trimester of pregnancy. Elevated maternal anxiety may negatively affect childbirth preparedness and pregnancy outcomes. Husband support has been recognized as an important psychosocial factor that may reduce maternal anxiety and enhance readiness for childbirth. However, evidence regarding the relationship between husband support, anxiety, and childbirth preparedness remains limited in primary healthcare settings. Purpose: To examine the relationship between husband support, maternal anxiety level, and childbirth preparedness among third-trimester pregnant women. Methods: A quantitative analytical study with a cross-sectional design was conducted from February to March 2025 at the Cipondoh Public Health Center. A total of 88 third-trimester pregnant women were recruited using purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected using structured questionnaires assessing husband support, maternal anxiety level, and childbirth preparedness. Descriptive statistics were used to summarize respondents' characteristics, while the Chi-square test was performed to determine the associations between husband support, anxiety level, and childbirth preparedness. Statistical significance was established at p < 0.05. Results: Most respondents were aged 21–35 years (83.0%), had completed senior high school education (51.1%), were employed (84.1%), and were primigravida (55.7%). Significant associations were found between husband support and maternal anxiety level (p < 0.001), maternal anxiety level and childbirth preparedness (p < 0.001), and husband support and childbirth preparedness (p < 0.001). Women who received husband support were more likely to experience mild anxiety and demonstrate better preparedness for childbirth than those who did not receive support. Conclusion: Husband support is significantly associated with lower maternal anxiety and improved childbirth preparedness among third-trimester pregnant women. Strengthening husband involvement during antenatal care may contribute to better maternal psychological well-being and enhance preparedness for childbirth.